Bidirectional Virtual Inertia Control Strategy for Hybrid Distributed Generations Integrated Distribution Systems. (8th November 2022) - Liu, Dan; Ye, Chang; Wu, Yingzi; Ji, Xiaotong; Xia, Yongjun; Kang, Yiqun; Liu, Ziwen
Abstract : The bidirectional ac/dc converter between the ac and dc subgrids plays a crucial role in enhancing the inertia support ability and ensuring the stable operation of the hybrid ac/dc distribution systems. In this paper, the bidirectional virtual inertia control strategy of hybrid distributed generations (DGs) integrated distribution systems is proposed for desired inertia support ability of both ac frequency and dc voltage. Firstly, the active power droop characteristics of the bidirectional ac/dc converter are analyzed, which reveals the steady power-sharing relationship between the ac and dc subgrids. Then, based on the dynamic power balance of the bidirectional ac/dc converter, the bidirectional virtual inertia control is proposed by introducing the virtual capacitor and moment of inertia, which can enhance the interactive inertia support ability of the hybrid distribution system. Finally, the effectiveness of the proposed control scheme is verified with a hybrid DGs integrated distribution simulation system in the PSCAD platform.